Retrospective Analysis of Clinical Outcomes Associated With the Use of Pegfilgrastim On-body Injector in Patients Receiving Chemotherapy Requiring Granulocyte Colony-Stimulating Factor Support. (April 2021) - Patel, Jolly; Rainess, Rebecca Ann; Benfield, Miranda J.; Rogers, Kate M. L.; Moore, Donald C.; Larck, Chris; Arnall, Justin R.
Objectives: Pegfilgrastim is a granulocyte colony-stimulating factor (G-CSF) used as primary prophylaxis in patients receiving myelosuppressive chemotherapy regimens that have greater than 20% risk of developing febrile neutropenia (FN). Historically, pegfilgrastim has been administered 24 to 72 hours after chemotherapy, necessitating a return to clinic to receive the provider-administered injection. An alternative option is the pegfilgrastim on-body injector (OBI). With the OBI device, patients have their pegfilgrastim administered 27 hours after receiving chemotherapy while remaining at home, avoiding an additional clinic appointment. Concerns with pegfilgrastim OBI include lack of experience with the device in both the patient and provider, device-related failures, and the success of delivery. This study evaluates pegfilgrastim OBI failure rates through associated patient outcomes among cancer patients receiving chemotherapy requiring G-CSF.Methods: A retrospective electronic chart review was conducted of adult patients with cancer who received chemotherapy and pegfilgrastim OBI from July 1, 2016, to July 31, 2018. The primary objective of this study was the incidence of FN in patients receiving pegfilgrastim OBI.Results: There were no reported cases of hospitalization due to FN in patients who received pegfilgrastim OBI. Dose delays and dosage modifications were not observed in our review. The OBI device failure rate was found to be low (1.92%).Conclusion: The low device failure rate from this study suggests that the OBI is a viable option for administration of pegfilgrastim in patients receiving chemotherapy requiring G-CSF.